1997
DOI: 10.1177/0044118x97029001004
|View full text |Cite
|
Sign up to set email alerts
|

Relational Problems with Peers, Gender, and Delinquency

Abstract: Although there is some evidence to suggest that classic strain theory is applicable to both male and female delinquency, several theorists have argued that a distinct version of strain theory may be required to explain delinquency among females. In particular, whereas male deviance tends to be generated by classic (or economic) strain, female deviance tends to be generated by strain occurring in interpersonal relations. This study attempts to test this argument by examining the relative effects of interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 47 publications
10
146
1
1
Order By: Relevance
“…Other studies indicated that while strain was relevant to both genders, there were some noteworthy differences in the causal processes. Findings reported by Agnew and Brezina (1997) revealed that strain was correlated with both male and female delinquency, but the association was stronger among males. Hay (2003) reported a similar gender differential in his examination of the associations between family strain and delinquency.…”
Section: Previous Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies indicated that while strain was relevant to both genders, there were some noteworthy differences in the causal processes. Findings reported by Agnew and Brezina (1997) revealed that strain was correlated with both male and female delinquency, but the association was stronger among males. Hay (2003) reported a similar gender differential in his examination of the associations between family strain and delinquency.…”
Section: Previous Researchmentioning
confidence: 91%
“…As noted, to date the majority of the research on GST concentrated on the young, primarily adolescents (Agnew & Brezina, 1997;Agnew, Brezina, Wright, & Cullen, 2002;Agnew & White, 1992;Aseltine, Gore, & Gordon, 2000;Hay, 2003;Hoffmann & Cerbone, 1999;Hoffmann & Su, 1997;Mazerolle, 1998;Mazerolle, Burton, Cullen, Evans, & Payne, 2000;Mazerolle & Maahs, 2000;Paternoster & Mazerolle, 1994;Piquero & Sealock, 2000, 2004. So far GST has enjoyed a fair amount of support in the research that focused on adolescents.…”
Section: Previous Researchmentioning
confidence: 99%
“…Official statistics reveal that males are initiated into and commit the majority of their crimes in male peer groups (Snyder 2000). Moreover, unresolved emotions, such as anger, coupled with increased exposure to delinquent peers, can further exacerbate the risk that a youth who has experienced trauma will in turn react with violence (Agnew and Brezina 1997).…”
Section: Introductionmentioning
confidence: 99%
“…premises of GST, interpersonal strains were found to be more pronounced for male delinquency [40]. In another study, Piquero and Sealock [41] found that depression did not influence either interpersonal or property offending.…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 94%